Increased fiber density of the fornix in patients with chronic tinnitus revealed by diffusion-weighted MRI - Rosemann, Stephanie; Rauschecker, Josef P. (Frontiers in Neuroscience, 2023)
Up to 45% of the elderly population suffer from chronic tinnitus -the phantom perception of sound that is often perceived as ringing, whistling, or hissing "in the ear" without external stimulation. Previous research investigated white-matter changes in tinnitus patients using diffusion-weighted magnetic resonance imaging (DWI) to assess measures such as fractional anisotropy (a measure of microstructural integrity of fiber tracts) or mean diffusivity (a measure for general water diffusion). However, findings overlap only minimally and are sometimes even contradictory. We here present the first study encompassing higher diffusion data that allow to focus on changes in tissue microstructure, such as number of axons (fiber density) and macroscopic alterations, including axon diameter, and a combination of both. In order to deal with the crossing-fibers -problem, we applied a fixel-based analysis using a constrained spherical deconvolution signal modeling approach. We investigated differences between tinnitus patients and control participants as well as how cognitive abilities and tinnitus distress are related to changes in white matter morphology in chronic tinnitus. For that aim, 20 tinnitus patients and 20 control participants, matched in age, sex and whether they had hearing loss or not, underwent DWI, audiometric and cognitive assessments, and filled in questionnaires targeting anxiety and depression. Our results showed increased fiber density in the fornix in tinnitus patients compared to control participants. The fornix, as a major output pathway of the hippocampus, constitutes an important part of the limbic system. The observed changes might, therefore, reflect compensatory structural alterations related to the processing of negative emotions or maladaptive changes related to the reinforced learning of the accompanying chronic tinnitus sensation. Due to the low sample size, the study should be seen as a pilot study that motivates further research to investigate underlying white-matter morphology alterations in tinnitus.